2009
DOI: 10.1007/s11426-009-0249-y
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of the glucose sensor based on three-dimensional ordered macroporous gold film and room temperature ionic liquid

Abstract: A novel type of glucose sensor was fabricated based on a glucose oxidase (GOD)-N,N-dimethtylformamide (DMF)-[BMIm][BF 4 ] composites modified three-dimensional ordered macroporous (3DOM) gold film electrode. The immobilized GOD exhibits a pair of well-defined reversible peaks in 50 mM pH 7.0 phosphate buffer solutions (PBS), which could be attributed to the redox of flavin adenine dinucleotide (FAD) in GOD. The research results show that ionic liquid ([BMIm][BF 4 ]), DMF and 3DOM gold film are crucial for GOD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…The initial studies with GF electrodes have shown very promising limits of detection; typically 10-100 times lower than the EPPG electrode. Note that traditional disc electrodes modified with porous layers have also been shown to give well defined voltammetry peaks leading to better detection limits [30][31][32][33]. This has recently been simulated and explained in detail by Compton and co-workers [34].…”
Section: Limit Of Detectionmentioning
confidence: 87%
“…The initial studies with GF electrodes have shown very promising limits of detection; typically 10-100 times lower than the EPPG electrode. Note that traditional disc electrodes modified with porous layers have also been shown to give well defined voltammetry peaks leading to better detection limits [30][31][32][33]. This has recently been simulated and explained in detail by Compton and co-workers [34].…”
Section: Limit Of Detectionmentioning
confidence: 87%
“…In this case, viscous IL consisting of charged species serves as a binder making film mechanically stable. The immobilized conducting elements include the following: multiwalled carbon nanotubes (MWCNTs) [38,93,[104][105][106][107][108], amine-functionalized MWCNTs [109], single-walled carbon nanotubes (SWCNTs) [110][111][112], porous carbon nanofibers [113], graphenes [114], polymer-functionalized graphene sheets [115], gold nanoparticles [116][117][118], PtCo alloy nanoparticles [67,119] and CdTe quantum dots [120]. Perhaps strong interactions between nanoobjects and IL components result in stable film formation and decrease their aggregation enhancing their electrocatalytic reactivity.…”
Section: Film Electrodes With Ionic Liquid As One Of the Componentsmentioning
confidence: 99%
“…Other group of IL containing composite film electrodes modified with horseradish peroxidase [27], hemoglobin [80,86,90,91,128], cytochrome c [116] or chloroperoxidase [81] exhibits catalysis of dioxygen reduction. Direct electrochemistry of another important enzyme, glucose oxidase immobilized on film electrode containing IL [38,114,117,138,139,158,163] or its mixture with dimethylformamide [117,158,163], was also reported. These and other electrodes were applied for bioelectrocatalysis of glucose [38,75,114,117,119,123,138,138,158,163,164].…”
Section: Film Electrodes With Ionic Liquid As One Of the Componentsmentioning
confidence: 99%
“…Moreover, the previously reported τ* for enzymatic and hemebased-biosensors that included BMIMBF4 ranged from 4.18 × 10 −12 to 9.07 × 10 −9 mol/cm 2 and 1.39 × 10 −11 to 6.81 × 10 −8 mol/cm 2 , respectively (Tables 1S-2S, Supplementary Material). Both lowest values of surface coverage were obtained for biosensors that did not include nanomaterials in their construction [51,52]. On the other hand, the higher loadings were reported when enzyme immobilization involved carbon nanomaterials [31,53].…”
Section: Direct Electron Transfer Behavior Of Nor On the Pge/[mwcnts/mentioning
confidence: 94%